Effectiveness of Shade and Cocopeat as a Growing Media for Acclimatization of Barangan Banana (Musa acuminate lin) Plants - Aprianto Aprianto; Chairani Hanum; Mukhlis Mukhlis (Jurnal Penelitian Pendidikan IPA, 2023)
The Effect of Shade and Cocopeat as a Growing Media on the Growth of Barangan Banana (Musa Acuminte Lin) at the acclimatization stage. Bananas are a superior commodity and the provision of quality seeds is important, so it is important to achieve the problem of planting media and providing shade at the acclimatization stage of young plants. The purpose of this study was to evaluate the provision of shade and the effectiveness of cocopeat as a planting medium for Barangan bananas at the acclimatization stage. This research was conducted in an open field, Medan Marelan, North Sumatra in September-November 2021. The study used a split plot design with the main plot providing shade at two levels, namely without shade and 50% paranet shade and cocopeat as a subplot with 5 levels, namely 100%. cocopeat, 100% topsoil, 75% cocopeat; 25% topsoil, 50% cocopeat: 50% topsoil, and 25% cocopeat: 75% topsoil. Data processing using ibm spss statistics software. The effect of shading was significantly different on the observation of plant height, number of leaves, stem diameter, leaf thickness and shoot dry weight. The use of 25% cocopeat: 75% topsoil increases the vegetative growth of plants in the number of leaves, stem diameter and plant chlorophyll. The interaction without shade and the effectiveness of cocopeat as a planting medium was significantly different where plants using 25% cocopeat: 75% topsoil and without shelter showed better vegetative growth compared to plants with shade and other cocopeat ratios. From the results, the best results show that the average use of 25% cocopeat compared to 75% soil shows that plants can grow optimally when the planting medium has good porosity